Effect of Liver Fatty Acid Binding Protein (L-FABP) Gene Ablation on Lipid Metabolism in High Glucose Diet (HGD) Pair-Fed Mice - McIntosh, Avery L. (Biochim Biophys Acta Mol Cell Biol Lipids, 2019)
Liver fatty acid binding protein (L-FABP) is the major fatty acid binding/”chaperone” protein in hepatic cytosol. Although fatty acids can be derived from the breakdown of dietary fat and glucose, relatively little is known regarding the impact of L-FABP on phenotype in the context of high dietary glucose. Potential impact was examined in wild-type (WT) and Lfabp gene ablated (LKO) female mice fed either a control or pair-fed high glucose diet (HGD). WT mice fed HGD alone exhibited decreased whole body weight gain and weight gain/kcal food consumed—both as reduced lean tissue mass (LTM) and fat tissue mass (FTM). Conversely, LKO alone increased weight gain, lean tissue mass, and fat tissue mass while decreasing serum β-hydroxybutyrate (indicative of hepatic fatty acid oxidation)—regardless of diet. Both LKO alone and HGD alone significantly altered the serum lipoprotein profile and increased triacylglycerol (TG), but in HGD mice the LKO did not further exacerbate serum TG content. HGD had little effect on hepatic lipid composition in WT mice, but prevented the LKO-induced selective increase in hepatic phospholipid, free-cholesterol and cholesteryl-ester. Taken together, these findings suggest that high glucose diet diminished the effects of LKO on the whole body and lipid phenotype of these mice.